2022
DOI: 10.1007/s00453-022-01007-w
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms and Complexity on Indexing Founder Graphs

Abstract: We study the problem of matching a string in a labeled graph. Previous research has shown that unless the Orthogonal Vectors Hypothesis (OVH) is false, one cannot solve this problem in strongly sub-quadratic time, nor index the graph in polynomial time to answer queries efficiently (Equi et al. ICALP 2019, SOFSEM 2021). These conditional lower-bounds cover even deterministic graphs with binary alphabet, but there naturally exist also graph classes that are easy to index: For example, Wheeler graphs (Gagie et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…To have a poly-time indexing of G that can solve MEM finding in truly subquadratic time, it is necessary to constrain the family of graphs in question. Therefore, we now focus on Elastic Founder Graphs (EFGs), labeled DAGs supporting poly-time indexing for linear time queries [14]. We will show that the same techniques used to query if Q appears in EFG G can be extended to solve MEM finding on G with arbitrary length threshold κ.…”
Section: Mems With Threshold In Elastic Founder Graphsmentioning
confidence: 99%
See 2 more Smart Citations
“…To have a poly-time indexing of G that can solve MEM finding in truly subquadratic time, it is necessary to constrain the family of graphs in question. Therefore, we now focus on Elastic Founder Graphs (EFGs), labeled DAGs supporting poly-time indexing for linear time queries [14]. We will show that the same techniques used to query if Q appears in EFG G can be extended to solve MEM finding on G with arbitrary length threshold κ.…”
Section: Mems With Threshold In Elastic Founder Graphsmentioning
confidence: 99%
“…Equi et al [14] showed that the suffix tree of T 3 can be used to query string Q in G, taking time O(|Q|). We now extend this algorithm to find MEMs between Q and EFG G with threshold κ and spanning more than 3 nodes.…”
Section: A Co-linear Chaining On Strings Using Mems Gives Lcsmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea behind founder graphs is that a multiple alignment of few founder sequences can be used to approximate the input MSA, with the feature that each row of the MSA is a recombination of the founders. Unlike ED strings, that are believed not to be efficiently indexable [26] (and indeed their value is to enable fast on-line string matching algorithms), some subclasses of founder graphs are, and a recent line of research is devoted to constructing and indexing such structures [32,20]. Like founder graphs, ED strings support the recombination of different rows of the MSA between consecutive columns.…”
Section: Other Related Workmentioning
confidence: 99%
“…Due to the difficulty of string search in general graphs, Equi et al [14] studied graphs obtained from multiple sequence alignments (MSAs), where an MSA[1..m, 1..n] is a matrix composed of m aligned rows that are strings of length n, drawn from an alphabet Σ plus a special gap symbol −. As we describe in Section 2, any segmentation of an MSA naturally induces a graph consisting of labeled nodes, partitioned into blocks.…”
Section: Introductionmentioning
confidence: 99%